Impaired Mitochondrial Fat Oxidation Induces FGF21 in Muscle - Bolormaa Vandanmagsar; Jaycob D. Warfel; Shawna E. Wicks; Sujoy Ghosh; J. Michael Salbaum; David Burk; Olga S. Dubuisson; Tamra M. Mendoza; Jingying Zhang; Robert C. Noland; Randall L. Mynatt (Cell Reports, 2016)
Fatty acids are the primary fuel source for skeletal muscle during most of our daily activities, and impaired fatty acid oxidation (FAO) is associated with insulin resistance. We have developed a mouse model of impaired FAO by deleting carnitine palmitoyltransferase-1b specifically in skeletal muscle (Cpt1bm−/−). Cpt1bm−/− mice have increased glucose utilization and are resistant to diet-induced obesity. Here, we show that inhibition of mitochondrial FAO induces FGF21 expression specifically in skeletal muscle. The induction of FGF21 in Cpt1b-deficient muscle is dependent on AMPK and Akt1 signaling but independent of the stress signaling pathways. FGF21 appears to act in a paracrine manner to increase glucose uptake under low insulin conditions, but it does not contribute to the resistance to diet-induced obesity.